2022
DOI: 10.3390/foods11244034
|View full text |Cite
|
Sign up to set email alerts
|

Development of Histamine in Fresh and Canned Tuna Steaks Stored under Different Experimental Temperature Conditions

Abstract: Among biogenic amines, histamine is most frequently involved in foodborne intoxication. To evaluate histamine formation in tuna, several storage conditions were reproduced. An LC-MS/MS method was used for analytical determinations. Fresh tuna samples (not contaminated and grafted with tuna muscle naturally incurred with histamine at 6000 mg/kg) were stored at 4, 12, and 20 °C, and daily samples were collected for 6 days. The development of histamine was observed only in grafted tuna samples. At 4 °C, histamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…This could be related to the possible microbial contamination and proliferation occurring during the handling and storage of the final product [ 41 , 42 , 43 ]. More specifically, as far as histamine is concerned, a BA that derives from the decarboxylation of the essential amino acid (EAA) histidine ( Figure 1 ) [ 9 ], this nitrogenous compound was detected in all three different formulations ( Figure 4 ), and its intake is mainly involved with the development of allergic phenomena and toxic reactions [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Currently, there are no guidelines regarding the concentration of BAs in foods; however, as far as histamine is concerned, literature studies have reported that quantities higher than 100 mg/kg can generally be considered potentially toxic, while other studies report harmful effects already starting from 50 mg/kg, recommending that the daily intake should not exceed this limit [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be related to the possible microbial contamination and proliferation occurring during the handling and storage of the final product [ 41 , 42 , 43 ]. More specifically, as far as histamine is concerned, a BA that derives from the decarboxylation of the essential amino acid (EAA) histidine ( Figure 1 ) [ 9 ], this nitrogenous compound was detected in all three different formulations ( Figure 4 ), and its intake is mainly involved with the development of allergic phenomena and toxic reactions [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Currently, there are no guidelines regarding the concentration of BAs in foods; however, as far as histamine is concerned, literature studies have reported that quantities higher than 100 mg/kg can generally be considered potentially toxic, while other studies report harmful effects already starting from 50 mg/kg, recommending that the daily intake should not exceed this limit [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…From this, it is clear how a high concentration of BAs in finished products could indicate contaminations likely occurring during the final steps of production or subsequent storage [ 41 , 42 , 43 ]. Higher BA content may result in a possible poor state of health of the animal, in that BAs are responsible for numerous adverse effects for the organism, from allergic reactions involving histamine [ 9 , 10 , 11 , 46 , 47 , 48 , 49 , 50 , 51 ] to numerous other types of toxic effects of which cadaverine, tyramine, tryptamine, phenethylamine, putrescine, spermidine, and spermine are responsible for [ 10 , 11 , 12 , 13 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…We investigate the optimal LFIA conditions to avoid nonspecific interactions and cross-reactivity. As a proof-of-concept, we evaluate the method in canned tuna as the food matrix. Tuna, belonging to the Scombroidae family, is characterized by high levels of histidine, which might be transformed to histamine throughout the food chain and canning process. , Remarkably, histamine presents high thermal stability, and therefore it might withstand food processing for canning . The amount of parvalbumin differs considerably among different fish species and tissues .…”
Section: Introductionmentioning
confidence: 99%
“…As a proof-of-concept, we evaluate the method in canned tuna as the food matrix. 44 46 Tuna, belonging to the Scombroidae family, is characterized by high levels of histidine, which might be transformed to histamine throughout the food chain and canning process. 44 , 47 Remarkably, histamine presents high thermal stability, and therefore it might withstand food processing for canning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation